Microsoft 70-332 : advanced solutions of SharePoint Server 2013. - Dye, David; Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"The new SharePoint Server 2013 Advanced Solutions Exam 70-332 course provides the knowledge and skills to configure and manage a SharePoint Server 2013 environment. This course will provide the necessary knowledge and skill sets to configure SharePoint Server 2013. In addition, you will gain guideline, consideration and best practices understanding concerning SharePoint Server 2013. For the Advanced Solutions course you will focus on implementing high availability, service application architecture, Business Connectivity Services, social computing features, business intelligence solutions, enterprise content management, web content management, apps and solutions. In addition to these focus areas you will also learn how to develop and implement a governance plan, how to perform an upgrade or migration and how to optimize the Search experience in SharePoint Server 2013."--Resource description page.
Presenter, David Dye.
Title and publication information from resource description page (Safari, viewed March 7, 2017).
Keywords: Microsoft SharePoint (Electronic resource); Intranets (Computer networks); Web servers; Client/server computing; Electronic data processing personnel -- Certification; Electronic books